Antimicrobial susceptibility of porcine Brachyspira hyodysenteriae and Brachyspira pilosicoli isolated in Sweden between 1990 and 2010 - Pringle Märit; Landén Annica; Unnerstad Helle; Molander Benedicta; Bengtsson Björn (Acta Veterinaria Scandinavica, 2012)
Abstract Background The anaerobic spirochetes Brachyspira hyodysenteriae and Brachyspira pilosicoli cause diarrheal diseases in pigs. Their fastidious nature has hampered standardization of methods for antimicrobial susceptibility testing. For monitoring of antimicrobial susceptibility wild type cutoff values are needed to define where the wild type distribution of MICs ends and no approved cutoffs are available for Brachyspira spp. In this study antimicrobial susceptibility data for both species (in total 906 isolates) were compiled and analyzed and wild type cut off values for B. hyodysenteriae proposed. Methods The MICs of tiamulin, valnemulin, tylosin, tylvalosin, doxycycline and lincomycin were determined by broth dilution in brain heart infusion broth supplemented with 10% fetal calf serum. Results The compiled MICs from the broth dilution tests of the B. hyodysenteriae type strain, B78T (ATCC® 27164T), showed that the method yields reproducible results. In an international perspective the frequencies of isolates with decreased antimicrobial susceptibility were low among both B. hyodysenteriae and B. pilosicoli. However, in B. pilosicoli a constant level of 10-15% isolates with tiamulin MICs >4 μg/ml was detected between 2002 and 2010 and in B. hyodysenteriae a gradual increase in tiamulin MICs was seen between 1990 and 2003 although this increase has ceased during the last years. The wild type cutoff values proposed for B. hyodysenteriae are: tiamulin >0.25 μg/ml, valnemulin >0.125 μg/ml, tylosin >16 μg/ml, tylvalosin >1 μg/ml, lincomycin >1 μg/ml and doxycycline >0.5 μg/ml. Conclusions The broth dilution method used in this study has over the years generated tightly grouped MIC populations for the field isolates and reproducible results for the control strain B78T and is therefore a suitable antimicrobial susceptibility test method for monitoring of Brachyspira spp. Here we propose wild type cutoff values for six antimicrobial agents for B. hyodysenteriae tested by broth dilution based on MIC distributions and the current knowledge on mechanisms of resistance in this species. There are few studies on antimicrobial resistance mechanisms and MIC distributions in B. pilosicoli but to some extent the cutoff values proposed for B. hyodysenteriae may be applicable also for monitoring of antimicrobial susceptibility in B. pilosicoli.